Trends in disease-modifying therapy use in patients with multiple sclerosis using a 10-year population-based cohort study in France. (4th May 2022) - Leblanc, Soline; Lefort, Mathilde; Le Page, Emmanuelle; Michel, Laure; Leray, Emmanuelle
ABSTRACT: Background: The availability of new disease-modifying therapies (DMTs) for patients with multiple sclerosis (MS) provides an opportunity for improving outcomes but makes disease management more complex. Our study aimed to describe changes in therapeutic practices over the period 2009–2018 and measure the impact of the arrival of oral DMTs on the use of injectable DMTs. Methods: Data were extracted from a representative 1/97 sample of the French population covered by the healthcare insurance system. Study period was set from 1 January 2009 to 31 December 2018. Four periods of MS identification were defined (before 2009, 2009–2011, 2012–2015, and 2016–2018). Results: Overall, 1, 508 patients with MS were included, of whom 876 (58.1%) were treated at least once over the study period. Untreated patients were older and had more comorbidities than treated ones. First-line DMTs were the most frequent initial DMT (78.5%), and a shift has operated from injectable to oral drugs over time. The proportion of patients receiving several DMTs increased with the number of available drugs. End 2018, relative parts of all DMTs were almost equal. Conclusions: This study provides valuable insights into the real-world use of DMTs and changes that have operated over time.